Sex Differences in the Non-infarct-Related Artery-Based Quantitative Flow Ratio in Patients With ST-Elevation Myocardial Infarction: A Retrospective Study - Hou, Hongli; Zhao, Qi; Qu, Chao; Sun, Meng; Liu, Qi; Huang, Xingtao; Wang, Xuedong; Zhang, Ruoxi; Du, Lifeng; Hou, Jingbo; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Introduction: It has been reported that sex has well-established relationships with the prevalence of coronary artery disease (CAD) and the major adverse cardiovascular events. Compared with men, the difference of coronary artery and myocardial characteristics in women have effects on anatomical and functional evaluations. Quantitative flow ratio (QFR) has been shown to be effective in assessing the hemodynamic relevance of lesions in stable coronary disease. However, its suitability in acute myocardial infarction patients is unknown. This study aimed to evaluate the sex differences in the non-infarct-related artery (NIRA)-based QFR in patients with ST-elevation myocardial infarction (STEMI). Methods: In this study, 353 patients with STEMI who underwent angiographic cQFR assessment and interventional therapy were included. According to contrast-flow QFR (cQFR) standard operating procedures: reliable software was used to modeling the hyperemic flow velocity derived from coronary angiography in the absence of pharmacologically induced hyperemia. 353 patients were divided into two groups according to sex. A cQFR ≤0.80 was considered hemodynamically significant, whereas invasive coronary angiography (ICA) luminal stenosis ≥50% was considered obstructive. Demographics, clinical data, NIRA-related anatomy, and functional cQFR values were recorded. Clinical outcomes included the NIRA reclassiﬁcation rate between men and women, according to the ICA and cQFR assessments. Results: Women were older and had a higher body mass index (BMI) than men. The levels of diastolic blood pressure, troponin I, peak creatine kinase-MB, low-density lipoprotein cholesterol, N terminal pro B-type natriuretic peptide, stent diameter, and current smoking rate were found to be significantly lower in the female group than in the male group. Women had a lower likelihood of a positive cQFR ≤0.80 for the same degree of stenosis and a lower rate of NIRA revascularization. Independent predictors of NIRA revascularization included sex, BMI, and high-density lipoprotein cholesterol. The area under the curve using cQFR ≤0.80 for NIRA revascularization was 0.984. Conclusions: cQFR values differ between the sexes, as women have a higher cQFR value for the same degree of stenosis. The ﬁndings suggest that QFR variations by sex require speciﬁc interpretation, as these differences may affect therapeutic decision-making and clinical outcomes.